Crop insurance: A barrier to conservation adoption?. (15th December 2020) - Fleckenstein, Michelle; Lythgoe, Ashlyn; Lu, Junyu; Thompson, Nathan; Doering, Otto; Harden, Seth; Getson, Jackie M.; Prokopy, Linda
Abstract: Midwest corn producers face inherent risks in their daily operations and incorporate risk-management strategies to reduce uncertainty; among these, crop insurance has dominated the agricultural landscape for decades. Previous research on conservation adoption has primarily examined the impact of individual-level characteristics on adoption, yet little is known about the impact of external factors, such as crop insurance. Using a mixed-methods approach, we conducted semi-structured interviews and a multi-state survey to determine if crop insurance requirements limit cover crops and/or conservation tillage adoption for Midwest corn producers. Our findings indicate that crop insurance requirements are not a barrier to adoption. Rather, crop insurance and conservation practices serve unique - not contradictory - roles in Midwest producers' operations and are used simultaneously. Future research should continue to identify and seek solutions for external barriers to broadly increase adoption rates. Highlights: Existing research is limited regarding the impact of crop insurance on conservation adoption.. We found that federal crop insurance is not a barrier to conservation adoption. Midwest producers engage in these behaviors simultaneously.